International economic negotiations : 2001 and beyond : an RNM commentary (Regional Negotiating Machinery LondonGB, 2001)
Presents relevant assessments, reports and analyses in respect of the principal areas of negotiation viz. FTAA, ACP-EU process; WTO issues and bilaterals i.e. CARICOM-Cuba and CARICOM-Canada.
Keywords: TRADE NEGOTIATIONS